Figurative Language Used in the Characterization of Katherine Applegate's Home of the Brave - Sari, Rizky Yunita; Wilujeng, Lilis Lestari (Jurnal Pembelajaran Sastra, 2021)
This paper depicts the types and uses of figurative expressions in the characterization of verse-novel Home of the Brave by Katherine Applegate. The objectives of this study are, first, to identify what kinds of figurative language the author uses in the story and second, to identify the use of figurative language in the characterization. As a descriptive qualitative study, the writers applied various literary theories such as figurative language (metaphor, simile, and personification), direct characterization, and stylistics. After analyzing the data, the writer found that there are 292 figurative languages found in the verse-novel Home of the Brave, which include: 89 metaphors, 98 similes and 105 personifications. Based on the findings, personification is mostly found throughout the story and the author mostly uses natural elements as comparison. The writer found that the use of personification is suitable for delivering story from narrator’s perspective because he is an immigrant from Sudan who can hardly understand the concept of many unfamiliar things in America. By linking human nature, he describes the world he sees and personifies it. Besides, it also proves that the use of figurative language is successfully employed by the novel’s author in the portrayal of characters physically and mentally as narrated by Kek as the main character of the story, in the view of the first person.